Antibacterial activity of bile on Escherichia coli and Salmonella spp isolated from faeces, urine and blood. - I.U., Nwankwo,; N, Amaechi,; R. C, Osaro-Matthew,; I. L, Obasi, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The antibacterial activity of bile on Escherichia coli and Salmonella spp isolated from faeces,urine and blood was determined in this study. Bile from three animal origin (cow ,goat andchicken) was extracted using alcohol and water and their antibacterial activity tested using theagar well diffusion method at different concentrations . The crude extracts exerted the highestinhibition zone diameter within the range of 20mm-49mm and 38mm-48mm against Salmonellaspp and Escherichia coli respectively, followed by the alcoholic extract with inhibition zonediameter in the range of 6mm-35mm and 7mm-33mm against Salmonella spp and Escherichiacoli respectively. While the aqueous extract exhibited the least activity in the range of 5mm-25mm and 7mm- 25mm against Salmonella spp and Escherichia coli respectively. The MIC ofthe bile extracts which was determined using the tube macrodilution method and the MBCshowed that bile have both bactericidal and bacteriostatic activity on the test organisms. Thefindings of this work has shown that bile contains some substances that can exert inhibitoryeffect on bacteria hence can be employed in the treatment of diseases caused by these groups ofbacteria.